Synthesis and determination of acute and chronic pain activities of 1-[1-(3-methylphenyl) (tetralyl)]piperidine as a new derivative of phencyclidine via tail immersion and formalin tests - Ahmadi, Abbas; Khalili, Mohsen; Mihandoust, Farnaz; Barghi, Leila (Arzneimittelforschung, 2010)
Phencyclidine (1-(1-phenylcyclohexyl)piperidine, CAS 956-90-1, PCP, I) and ketamine (2-O-chlorophenyl-2-methylamino-cyclohexan, CAS 1867-66-9, II) revealed some analgesic effects. Some of their derivatives have been synthesized for biological properties studies. Utilizing 1-tetralone as a starting material, 1-[1-(3-methylphenyl)(tetralyl)]piperidine, (PCP-CH3-tetralyl, III) was synthesized and its analgesic effects were studied on rats via tail immersion (as a model of acute thermal pain) and formalin (as a model of acute chemical and chronic pain) tests and compared with those of ketamine and PCP. The results indicated a marked anti-nociception 2-25 min after ketamine injection, but this analgesic effect lasted for 40 min following PCP-CH3-tetralyl application in the tail immersion test. However, the data obtained from the formalin test showed that chronic pain could be significantly attenuated by ketamine, PCP and PCP-CH3-tetralyl.
Keywords: CAS 956-90-1; CAS 1867-66-9; Ketamine; Phencyclidine; 1-Tetralone derivatives, analgesic effects, formalin test, tail immersion test